The Arab Maghreb Union: Regionalization without integration - Baghdadi, Leila; Karray, Zouhour; Zaki, Chahir (2021)
Leila Baghdadi, Zouhour Karray and Chahir Zaki POLICY SEMINAR Making the most of intra-African trade: the 2021 Africa Agriculture Trade Monitor Co-Organized by IFPRI and AKADEMIYA2063 SEP 23, 2021 - 09:30 AM TO 11:00 AM EDT